Impossible views of the world / Lucy Ives. - Ives, Lucy, 1980- (Penguin Press, 2017)
"A witty, urbane, and sometimes shocking debut novel, set in a hallowed New York museum, in which a co-worker's disappearance and a mysterious map change a life forever Stella Krakus, a curator at Manhattan's renowned Central Museum of Art, is having the roughest week in approximately ever. Her soon-to-be ex-husband (the perfectly awful Whit Ghiscolmbe) is stalking her, a workplace romance with "a fascinating, hyper-rational narcissist" is in freefall, and a beloved colleague, Paul, has gone missing. Strange things are afoot: CeMArt's current exhibit is sponsored by a Belgian multinational that wants to take over the world's water supply, she unwittingly stars in a viral video that's making the rounds, and her mother--the imperious, impossibly glamorous Caro--wants to have lunch. It's almost more than she can overanalyze. But the appearance of a mysterious map, depicting a 19th-century utopian settlement, sends Stella--a dogged expert in American graphics and fluidomanie (don't ask)--on an all-consuming research mission. As she teases out the links between a haunting poem, several unusual novels, a counterfeiting scheme, and one of the museum's colorful early benefactors, she discovers the unbearable secret that Paul's been keeping, and charts a course out of the chaos of her own life. Pulsing with neurotic humor and dagger-sharp prose, Impossible Views of the World is a dazzling debut novel about how to make it through your early thirties with your brain and heart intact"--